2022
DOI: 10.1007/s00417-022-05578-w
|View full text |Cite
|
Sign up to set email alerts
|

Acute intraocular toxicity caused by perfluorocarbon liquids: safety control systems of medical devices

Abstract: Background Acute retinal toxicity has been demonstrated to be associated with the intraoperative use of perfluorocarbon liquids (PFCLs), especially perfluorooctane (PFO). Recently, several cases of PFO-associated blindness have been reported in Spain, Holland, France, Italy, the Middle East, and South America. Methods As a result, a new ISO guideline ( ISO 16672:2020) was drafted, discussed, approved, and released in 2019. This recent ISO16672… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 26 publications
0
1
0
1
Order By: Relevance
“…One of the main disadvantages of PFCLs is that they are approved only for intra-operative use only, since many animal studies have indicated that leaving PFCL in the vitreous cavity as a post-operative tamponade agent causes retinal toxicity [ 144 , 145 , 146 ]. It is not completely clear where PFCL’s toxicity stems from, but it has been shown that it could be a combination of induced inflammation, impurities and chemical toxicity and mechanical trauma, not only in the long term but also acutely [ 147 , 148 , 149 , 150 ]. Some of these impurities have been identified as molecules with nitrogen bonds, as well as compounds containing hydrogen and fluoride [ 151 , 152 ].…”
Section: Classification Of the Vitreous Substitutes: General Principl...mentioning
confidence: 99%
“…One of the main disadvantages of PFCLs is that they are approved only for intra-operative use only, since many animal studies have indicated that leaving PFCL in the vitreous cavity as a post-operative tamponade agent causes retinal toxicity [ 144 , 145 , 146 ]. It is not completely clear where PFCL’s toxicity stems from, but it has been shown that it could be a combination of induced inflammation, impurities and chemical toxicity and mechanical trauma, not only in the long term but also acutely [ 147 , 148 , 149 , 150 ]. Some of these impurities have been identified as molecules with nitrogen bonds, as well as compounds containing hydrogen and fluoride [ 151 , 152 ].…”
Section: Classification Of the Vitreous Substitutes: General Principl...mentioning
confidence: 99%
“…Eine Abgrenzung zu anderen Ursachen ist wesentlich, um den Einsatz gleicher Chargen bei anderen Patienten möglichst zu vermeiden. Eine toxikologische Untersuchung einer verdächtigen Charge sollte erfolgen 39 , 40 . Es besteht auch eine Variabilität bei Silikon für intraokulare Tamponaden, je nach Zusammensetzung beeinflusst dies potenziell zytotoxische Wirkungen 41 , 42 .…”
Section: Retinopathien Durch Exogen Zugeführte Substanzenunclassified